Changes in and associations between functional indices of young handball players` upper extremities when applying neuromuscular training - Lendraitiene, E.; Petkute, T.; Laurinaviciute, E. (Medicina dello Sport, 2021)
BACKGROUND: Neuromuscular training of the upper extremities has been demonstrated to improve functional indices and to be a trauma prevention measure in certain branches of sport, yet data on the effect of neuromuscular training on the indices of handball players` functional status are scarce.